The Impact Of Iraqi Local Accounting Standards On Earnings Management - Hadi Al-Zabari, Salim Awad; Hussein Al-Fatlawi, Ali Kadhim (Opción, 2019)
The article aims at verifying the hypothesis adopted by the researchers, which stated that the accounting standards in Iraq have repercussions on the earnings management, whether this reflection is positive or negative, especially that there is no formal disclosure of the company’s earnings management for achieving management objectives. The management of the company may wish to achieve a certain earning figure and then interpret the accounting standards in a manner commensurate with what it aspires to. The information available from the entity’s financial statements at the end of the accounting period has an impact on many conflicting stakeholders in the community, especially investors, consumers and creditors in the community. Hence, the management may use its creative practices to express the veracity of disclosures in financial statements. These methods may develop to conceal financial facts as a deterioration or failure of certain financial ratios and are contrary to accounting principles. Thus, the controversy over the counting of earnings management is a negative system that contradicts the eth- ics of the accounting profession. A positive form that takes advantage of the gaps that the financial accounting standards provide to modify and change the figures and financial statements in the interest of management. Through this paper, the researchers highlighted the concept and motives of earnings management as well as highlighting the ethical perspective of this practice by the management. The re- searchers have also dealt with an analytical study to link accounting standards and their impact on earnings management. The researchers then made their recommendations for the company’s man- agement to increase transparency and disclosure, which helps to reduce earnings management practices.